Forecasting Turkish Industrial Production Growth With Static Factor Models - Mahmut Günay (International Econometric Review (IER), 2015)
In this paper, we forecast industrial production growth for the Turkish economy using static factor models. We evaluate how the performance of the models change based on the number of factors we extract from our data as well as the level of aggregation for the series in the data set. We consider two evaluation samples for the out-of-sample forecasting exercise to assess the stability of the forecasting performance. We find that the effect of the data set size on the forecasting performance is not independent from the number of factors extracted from this data set. Rankings of the models change in different evaluation samples. We conclude that using a dynamic approach to evaluate models from different dimensions is important in the forecasting process.
Keywords: E37; C32; C33; 330; Forecasting; Factor Models; Principal Components